The Methods of Questioning in the Orientation Phase : A Review of Teaching Malaysian Gifted Learners in Reading Arabic Text - Damien, Mikeng; Muhammad Nazir, Alias; Mohd Sham, Kamis; Nik Mohd Rahimi, Nik Yusoff; Rorlinda, Yusof; Noriah, Mohd ishak (International Journal of Innovation, Creativity and Change (JICC), 2020)
Differentiated instruction allows gifted individuals to develop their potential academic intelligence to the highest level independently. The authors suggest how to use methods of questioning in the orientation phase for teaching Malaysian Gifted Learners in comprehending Arabic text in the classroom. This includes identifying jumlah mufidah, jumlah ismiyyah and jumlah fi’liyyah. The use of the orientation phase "is the starting points to ensure what learners learn, how they learn the lesson, and how the learners demonstrate what they have learned during the teaching and learning session."